Convergence Results for Total Asymptotically Nonexpansive Monotone Mappings in Modular Function Spaces. (15th July 2021) - Rashid, Maliha; Kalsoom, Amna; Yao, Shao-Wen; Ghaffar, Abdul; Inc, Mustafa
Abstract : In this article, we consider an extensive class of monotone nonexpansive mappings. We use S -iteration to approximate the fixed point for monotone total asymptotically nonexpansive mappings in the settings of modular function space.